Overview of the existing heat storage technologies: sensible heat - Sergii Bespalko; Alberto Munoz Miranda; Oleksii Halychyi (ACTA INNOVATIONS, 2018)
Over the past several decades, much attention has been given to the development of technologies utilizing solar energy to generate inexpensive and clean heat for heating purposes of buildings and even for electricity generation in the concentrating solar thermal power (CSTP) plants. However, unlike conventional heatgenerating technologies consuming coal, natural gas, and oil, heat produced by solar energy is intermittent because it is significantly affected by daily (day-night) and seasonal fluctuations in solar insolation. This fact issues a considerable challenge to the adoption of solar energy as one of the main renewable heat sources in the future. Therefore, along with the development of the different solar technologies, the heat storage technologies have also been the focus of attention. Use of the storage devices, able to accumulate heat, enables not only enhance the performance of the heating systems based on solar energy but also make them more reliable.